Dendrochronology of young Swietenia macrophylla and the variation of its growth response to the past wet climate in Bengkulu, Indonesia - AGUS SUSATYA; YANSEN YANSEN (Society for Indonesian Biodiversity, 2016)
Susatya A, Yansen. 2016. Dendrochronology of young Swietenia macrophylla and the variation of its growth response to the past wet climate in Bengkulu, Indonesia. Biodiversitas 17: 466-472. Dendrochronology had long been studied in temperate regions to know tree growth responses to the past climate, and to predict the future effects of climate change. In the wet tropics, dendrochronology studies were rarely carried out because of the lack of distinct annual growth rings or wide variation of growth ring forms. Our research was aimed to know the variations of width of growth rings, and growth response of young Big-Leaf Mahogany (Swietenia macrophylla) to the past wet climate in Bengkulu, Indonesia. Wood disc specimens of cross sections were collected from seven different mahogany trees from campus forest, University of Bengkulu, and then were dried, sanded, and digitally photographed. Growth rings were measured to the nearest 0.001 cm with ImageJ software. The annual ring width data were cross-dated visually by synchronizing and aligning the width patterns of all wood specimens. The results showed that the average of annual growth rings varied from 0.679 cm/year to 1.047 cm/year, and was not significantly different among trees. The width of growth ring of Big-Leaf Mahogany trees demonstrated periodicity through ages, and increased until 9 years old and then started to decline. Individual tree responded differently to climate through out the ages. In the stand level, the average annual growth ring was very sensitive to climate, and positively correlated to rainfall in the first six years, but was independent to rainfall in the past five years. It was speculated that local environments and ecological processes were attributed to obscure the influence of rainfall to the annual growth ring of the older stand.